pelaksanaan kewajiban menyelesaikan perkara di pengadilan industrial dalam waktu 50 hari - PAHLEVI ISKANDAR, AKBAR; NUGROHO, ARINTO (NOVUM : JURNAL HUKUM, 2018)
The problems of industrial relations disputes are becoming increasingly complex and complex, so that rapid and appropriate, just, and inexpensive institutions and mechanisms for dispute settlement of industrial relations are needed. The word quickly must be interpreted as a strategic effort that makes the judicial system as an institution that can guarantee the achievement of justice in the rapid enforcement of law by the seeker of justice. the judicial process can take place quickly as described in Article 103 of the PPHI Law which gives a time limit of 50 days, but some decisions are cut over 50 days, the problems taken in this study How Implementation of Article 103 of Law Number 2 Year 2004 About Dispute Settlement Industrial Relations about the case which was decided at the latest within 50 days at the Surabaya Industrial Relations Court ?, What are the Constraints faced by the Surabaya Industrial Relations Court to run the trial process in accordance with the provisions of Article 103 of Law Number 2 of 2004?The type of research used is empirical law study that includes research on legal identification and research on legal effectiveness, using qualitative method that is data obtained, both primary and secondary, will be presented descriptively, and then given a conclusion, the data obtained by interview and documentation . The implementation of the obligation to settle the case in the Surabaya PHI has not been able to run maximally this is evidenced by the fact that the number of judgments exceeding the deadline of 50 days, the less than optimal implementation occurs due to various obstacles that resulted in the decision of the judges beyond the time limits set forth in theincluding constraints, among others, community factors such as awareness to attend the scheduled trial schedule, the readiness of the court file and the evidence that should be presented in the hearing. The absence of legal consequences resulting from a decision that exceeds the 50-day time limit and only the courts and the judges are being reprimanded by the Supreme Court so that the parties are minimally aware of the timely completion of industrial relations affairs.